THE INFLUENCE OF ORGANISATIONAL CULTURE AND LEADERSHIP STYLE ON EMPLOYEE PERFORMANCE IN FINANCING DISTRIBUTION WITH EMPLOYEE SATISFACTION AS AN INTERVENING VARIABLE AT PT PNM VENTURA SYARIAH - Trijaya, Engga; Safaria, Dra. Siti (UTSAHA: Journal of Entrepreneurship, 2023)
Business growth in the financial institution sector in Indonesia is currently providing stronger competition among similar industries. Then, PT PNM Ventura Syariah is working hard in improving the employee performance. The research population is all employees at PT PNM Ventura Syariah with a sample size that selected using proportional random sampling technique. The data obtained were analyzed using descriptive analysis and SEM PLS analysis. The objective of this research is to determine whether the variables of organisational culture, leadership style, and job satisfaction on employee performance. The research results indicated that organizational culture variable had no effect on employee performance, but the leadership style and job satisfaction variable has a positive effect on employee performance. In addition, organizational culture variables directly have a positive effect on job satisfaction, and leadership style variable has no effect on job satisfaction. Moreover, job satisfaction variable is not able to mediate the effect of organizational culture on employee performance. Then, job satisfaction variable is able to mediate the effect of leadership style on employee performance.